The right to the protection of personal data. Some relevant topics about its regulation in Peru - Eguiguren Praeli, Francisco José (2015)
What guarantees do we have as titleholders of theright to personal data protection? Does the Political Constitution of 1993 truly protect this right in aproperly way? Which role does the relatively recentPeruvian Law on the Personal Data Protection playto that effect?In this article, the renowned constitutionalist gives answers to these questions with a brief and detailed analysis of the Peruvian Law on the Personal Data Protection and its rules of procedure, focusing in its pros and cons, but also of the Peruvian National Personal  Data  Protection  Authority’s  role  and functions to that effect.